THE EFFECT OF JIGSAW METHOD ON THE ABILITY OF THE FIRST YEAR STUDENTS OF FARMASI VOCATIONAL HIGH SCHOOL IN COMPREHENDING DESCRIPTIVE TEXTS - Mifta, Rischa; Eliwarti, Eliwarti; Mulatif, Jis (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This research aimed to find out whether there is any significant effect of using jigsaw method on the students’ reading comprehension of descriptive texts. This research was conducted at Pharmacy Vocational High School Pekanbaru from November August to September 2018. The population was all of first year students in academic year of 2018/2019. The number of the entire population was 266. The writer used cluster random sampling technique to determine the sample. The participant of this research was 35 students of X.5 class. This research consisted of 6 experiment meetings. The instrument of the research was multiple choice test. In analyzing the data, the writer used a statistical analysis. The writer used t-test to compare the difference of students’ score in pre-test and post-test. The mean score of the students before the treatment was 67.8571. The mean score of the students after the treatment was 80.4286. Moreover, from the statistical analysis, it was found out the T-test score (11.7) was higher than T-table (1.69). The finding showed that there was significant effect of jigsaw method on the students reading comprehension of descriptive texts. Based on this finding, it is suggested that Jigsaw method can be used by the teacher as an alternative method in the teaching of reading.Key Words: Jigsaw Method, Reading Comprehension, Descriptive Texts.